Islam Nusantara dan Islam Berkemajuan: Perbandingan Perspektif Nahdlatul Ulama dan Muhammadiyah - Hartinawanti H; Indo Santalia; Andi Aderus (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article examines the two largest patterns of Islam in Indonesia, namely Nusantara Islam initiated by Nahdlatul Ulama (NU) and Progressive Islam developed by Muhammadiyah. Both represent the face of Indonesian Islam as moderate, inclusive, and adaptive to the socio-cultural context of the Nusantara. The study focuses on historical background, theological characteristics, da'wah approaches, points of similarity and methodological differences, as well as their relevance to national life. This research method uses a qualitative approach based on literature studies, analyzed descriptively and analytically with a comparative approach. This research method uses a qualitative approach based on literature studies, analyzed descriptively and analytically with a comparative approach.